Peran Kepala Sekolah Sebagai Manajer Dan Supervisor Dalam Implementasi Kurikulum Merdeka Di Sekolah Dasar - Sumarni; Siswoyo; M. Badrun (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the role of school principals in the implementation of the Independent Curriculum in State Elementary School, Pulau Panggung District. The background of this research is based on the challenges faced in the implementation of the Independent Curriculum, such as limited resources, lack of teacher training, and adaptation to innovative learning methods. The principal has a strategic role in supporting the implementation of this curriculum, both as managers, supervisors, and entrepreneurs in managing and developing learning media. This study uses a qualitative approach with a descriptive method. Data were obtained through interviews, observations, and documentation involving principals and teachers. The results of the study show that school principals have a significant role in directing, supervising, and optimizing the implementation of the Independent Curriculum. There are obstacles such as lack of technological skills, time constraints, and resistance to changes in the school environment. Therefore, increased training, closer collaboration between principals and teachers, and more comprehensive policy support are needed to overcome these obstacles. The leadership of the principal contributes greatly to the successful implementation of the Independent Curriculum, with a positive impact on the quality of learning.